Layerwise fabrication of refractory NiCrSiB composite with gradient grow of tungsten carbide additives by selective laser melting. (December 2019) - Shishkovsky, Igor; Kakovkina, Nina; Sherbakov, Vladimir
Highlights: Laser in-situ synthesis of gradient MMC was implemented. Self-fluxing NiCrSiB alloy was employed for powder bed fusion process. NiCrSiB alloy with gradient WC inclusions was evaluated for layerwise SLM process. Microhardness control via WC concentration content in MMC was demonstrated. Abstract: In the present paper, the selective laser melting process of multilayered 3D fabrication from metal matrix composites (MMC) based on nickel-chrome heat resistant alloy with WC ceramic reinforcing additive was implemented. The possibility of a laser powder bed fusion of functional grade (FG) 3D parts from these MMC for the account of increasing the alloying element concentration from 5% to 15%vol of the tungsten carbide in NiCrSiB self-fluxing alloy was shown. The optical and scanning electron microscopy, X-ray and EDX microanalysis, and microhardness measurements have been carried out to evaluate the structure formation features. We strongly recommend additional heating of the initially powdered mixture and/or substrate for temperature gradient reduction in the volume of the 3D part, homogenization of structure and decreasing residual stresses and propensity to delamination.